Optimasi Pola Tata Tanam untuk Peningkatan Luas Layanan pada Daerah Irigasi Saddang - Sulistyani, Kiki Frida; Irianto, Danang Bimo (Universitas Tribhuwana Tunggadewi Malang, 2021)
Daerah Irigasi (DI) Saddang berada di Kabupaten Pinrang Propinsi Sulawesi Selatan dengan luas areal 61.198 Ha, yang mendapatkan air dari Bendung Benteng memiliki debit rata-rata 319 m3/dt dan debit Andalan yang berfluktuasi antara 39,8 – 328,1 m3/dt. DI Sadang memiliki Pola Tata Tanam (PTT) eksisting Padi-Padi Palawija dengan awal tanam yang berbeda-beda pada setiap primer/sekundernya. Hasil perhitungan neraca air dengan PTT eksisting tanpa memperhitungkan debit pemeliharaan didapatkan areal yang terairi seluas 48.958 Ha di MT1 61.198 Ha di MT2 dan 61.198 ha di MT3 atau areal terairi 61.198 Ha dengan intensitas tanam 280%. Guna mengoptimalkan air yang ada maka dibuat PTT rencana, dengan mengeser awal musim tanam pada berbagai variasi. Dari hasil perhitungan dengan PTT rencana Padi-Padi-Palawija didapat bahwa air yang ada masih cukup untuk mengairi areal seluas 61.198 dengan intensitas tanam 300%. Kelebihan air yang ada, jika di manfaatkan untuk penambahan areal, didapat tambahan areal yang bisa terairi seluas 47.016 Ha dengan intensitas tanam 300%. Jadi secara perhitungan total, didapat areal terairi seluas 108.214 Ha dengan intensitas tanam 300%. Perhitungan ini juga tanpa mempertimbangkan debit pemeliharaan. Sesuai dengan peraturan yang ada, debit pemeliharaan tetap harus dialokasikan untuk kelestarian sungai. Perhitungan debit pemeliharaan dengan menggunakan metode Tennant, didapatkan debit pemeliharaan Bendung benteng adalah 31,9 m3/dt. Dari hasil analisa neraca air dengan memperhitungkan debit pemeliharaan didapatkan areal yang terairi dengan pola tanam Padi-Padi-Palawija adalah seluas 61.198 Ha di MT1 61.198 Ha di MT2 dan 16.523 ha di MT3 atau areal terairi 61.198 Ha dengan intensitas tanam 227 %. Terjadi penurunan intensitas tanam sebesar 53 % di banding pola tata eksisting.ABSTRACTThe Saddang Irrigation Area is located in Pinrang Regency, South Sulawesi Province with an area of 61,198 ha, which gets water from the Benteng Barrage, which has an average discharge of 319 m3/s and a fluctuating dependable flow between 39.8 - 328.1 m3/s Saddang Irrigation Area has an existing crop pattern of Paddy Paddy Palawija with different planting starts for each primary/secondary. The results of the calculation of the water balance with the existing cropping pattern without considering maintenance flow as an obligation that must be fulfilled, have a result it can irrigate 48.958 ha in Planting Season 1, 61.198 ha in planting season 2, and 61.198 ha in planting season 3, or irrigated 61.198 ha with 280% crop intensity. To optimize the available water, a planned crop pattern was created, by shifting the beginning of the planting season to various variations. From the results of calculations with the cropping pattern of the Paddy-Paddy-Palawija, it was found that the available water was still sufficient to irrigate an area of 61.198 ha with 300% crop intensity. If the excess water is used for additional areas, an additional area that can be irrigated is 47.016 ha with 300% crop intensity. So in the total calculation, the irrigated area is 108,214 ha with 300% crop intensity. This calculation is also without considering maintenance flow as an obligation that must be fulfilled. Under existing regulations, the maintenance flow must be allocated for river conservation. Calculation of the maintenance flow using the Tennant method, it is found that the maintenance discharge of the Benteng Barrage is 31.9 m3/s. From the results of the water balance analysis with maintenance flow as an obligation that must be fulfilled, from the calculation results obtained that the irrigated area with the Paddy-Paddy-Palawija cropping pattern, was 61.198 ha in planting season 1, 61.198 ha in planting season 2, and 16.523 ha in planting season 3, or 61.198 ha with 227% crop intensity. There was a 53 % decrease compared to the existing crop intensity.